Reflections of small homeland in the literary adopted math problems - Burneikaitė, Rima; Kašuba, Romualdas (Lietuvos matematikos rinkinys, 2013)
In the papers some aspects of possibly challenging and remarkably nice reflections of small homeland (or any other familiar environment corresponding "small fatherland" as the place where the given person feels itself home) via literary adopted math problems together with the possible advantages of the method are discussed.